THE USE OF THERAPEUTIC PLASMA EXCHANGE IN A PATIENT WITH RECURRENT SEVERE HYPERTRIGLYCERIDEMIA-INDUCED ACUTE PANCREATITIS - Ng, Wei Wei; Liew, Wai Leong (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Severe hypertriglyceridemia (HTG)-induced acute pancreatitis is defined by clinical, laboratory and radiographic evidence of acute pancreatitis with triglyceride (TG) levels of >11.2 mmol/L in the absence of other causative factors. We report a case of therapeutic plasma exchange (TPE) used in recurrent severe HTG-induced acute pancreatitis who failed conventional treatment. CASE The patient is a 28-year-old female with poorly controlled Type 2 diabetes mellitus diagnosed 4 years ago with HbA1c range of 10-13% despite on Insulin Actrapid 30 u three times daily, Insulin glargine 36 u daily and Metformin 1g twice daily. Her TG levels remained elevated despite being on daily 145 mg of Fenofibrate, 40 mg of Rosuvastatin, and 4 gm of Omega-3-free fatty acid. Xanthelasma, tuberous or tendon xanthomata were absent. She denied a family history of hypertriglyceridemia. She was nonalcoholic and her thyroid screen was normal. Obesity and poor compliance with lifestyle changes and medications alongside poorly controlled diabetes contributed to severe hypertriglyceridemia. She had recurrent admissions for severe HTG-induced acute pancreatitis within the past 2 years. During each admission, she was given supportive treatment including fasting with bowel rest, analgesia, intravenous hydration, and insulin infusion. She failed to respond to conservative measures and required TPE for 3 of her 6 admissions. Her TG level was >64 mmol/L during these 3 admissions with persistent severe abdominal pain lasting more than 48-72 hours despite fentanyl infusion. Fresh frozen plasma was used as replacement fluid during each TPE session. TG levels dropped by 80-85% after a single TPE with TG levels on discharge decreased to a range of 2.3-5.5 mmol/L. CONCLUSION This case highlights the potential utility of TPE during acute pancreatitis by rapidly decreasing TG levels and reducing inflammatory cytokines. However, the TPE effect is transient and the patient requires adequate lipidlowering treatment to achieve lasting effects.